Enhanced methane generation using zeolitic imidazolate framework (ZIF-8) during biogas production - Gracious Makuba; Idah Jim Calvin; Mercy Kiende; Martha N. Chollomo; Register Mrosso; Achisa C. Mecha (Discover Sustainability)
Abstract Metal–organic frameworks (MOFs) are increasingly being utilized in catalysis, fuel cells, and related fields due to their unique characteristics. This study explores the use of Zeolitic Imidazolate Framework-8 (ZIF-8) MOF during co-digestion of tuber and fruit waste to enhance biogas production and methane content. The ZIF-8 was synthesized and characterized using Fourier Transform Infra-Red spectroscopy, to confirm the presence of functional groups. The following properties of the feedstock and inoculum were evaluated: moisture content, volatile solids, total volatile solids, biodegradability index, total dissolved solids, pH, and electrical conductivity. The effect of solution pH and MOF mass was assessed. FTIR spectra were obtained with an FTIR spectrometer over a wavenumber range of 4500–500 cm⁻1. The pH values were near neutral, i.e., 6.9 (fruit waste), 6.7 (tuber waste), and 7.4 (inoculum). The biogas yield increased with ZIF-8 catalyst dosage, the highest biogas production of 1851 mL at ZIF-8 dosage of 0.5 g was attained which is twice as much as the control experiment (without ZIF-8) attained 914 mL. The use of ZIF-8 resulted in a 103% increase in biogas yield and showed that the application of ZIF-8 catalyzed the methanogenesis step resulting in increased yield and efficiency of the process.